A STUDY TO DETERMINE THE ORGANIZATIONAL JUSTICE PERCEPTIONS OF THE HEALTHCARE ORGANIZATIONS STAFF - Mesut ÇİMEN (Fırat University, 2019)
Organizational justice perception, which is formed according to the gains of the employees in the workplace, the distribution process of these gains, informing of the employees about these gains and behaviors of managers, are of great importance for healthcare organizations. In healthcare organizations which are defined as labor intensive services, perceptions, attitudes and behaviors of the workers are known to be directly related to organizational justice. The literature section of this study is aimed to clarify the concept and dimensions of organizational justice. In research part, the level of organizational justice the private healthcare staff had perceived and whether their organizational justice perception varies according to demographical characteristics are examined. The study took place in Istanbul, Kocaeli and Yalova between October, 2015 and January, 2016. Data were collected through surveys from i